Small islands: living laboratories revealing global climate and sustainable development challenges - Pathirana, Assela (Frontiers in Climate, 2025)
Small islands, while hosting only about 1% of the global population, are among the most vulnerable regions to climate change. Their critical importance in climate adaptation is often overlooked, and their value as natural laboratories is frequently lost in discussions on sustainable development and climate adaptation. Beyond their well-documented vulnerabilities, small islands serve as invaluable scientific laboratories, illustrating the interconnected impacts of water, environment, society, and economy. Due to their small size and “islandness,” these provide a condensed and accelerated view of natural and anthropogenic phenomena, which are harder to observe in larger, more distributed geographies. Investing in research and adaptation strategies for these communities addresses their immediate needs and offers critical insights and early warning signs for broader global climate challenges. This paper argues for increased attention and resources for small islands, emphasising their role as microcosms that reflect broader environmental trends and highlighting the urgent need for targeted adaptation measures.